STUDENTS’ RESPONSES TO EXTENSIVE READING ACTIVITIES IN ONLINE CLASSROOM - Thomas Wahyu Prabowo Mukti (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2022)
This pandemic has forced Book Report classes which are based on Extensive Reading Principles to be conducted online. This condition makes lecturers and students unable to conduct activities that are designed predominantly for offline classes. Therefore, the writer had to make some adjustments to the online learning environment. This practice is not yet studied extensively, hence, this paper aims to find out students’ perceptions related to extensive reading practices and how the implementation helps them learn English by analyzing data from Google Form, interview results, and lecturer’s notes and observation. The participants of this study are twenty-six students from Book Report D. The results of this study show students’ positive perception towards all activities in the class (ranging from 40.7% to 66.7% for each activity) and 96.3% of students considered they have positive progress from the beginning until the end of the class. These results show, that despite the challenges, educators should still apply extensive reading practices in their classes considering the benefits students could get from doing so.